Development of Distribution Center Leu Mart Karawang with Feasibility Analysis, SWOT, STP, IFE EFE IE and Marketing Mix 9P - Candra Galang Gemilang Putra; Wahyudin Wahyudin; Hamdani Hamdani (Jurnal Rekayasa Sistem & Industri, 2021)
MSMEs are Indonesia's largest financial access by contributing 60.34% of GDP (Gross Domestic Product).Seeing the very high number of markets with needs that must be met, the Leu Mart Karawang DistributionCanter (DC) was formed to bridge by cutting the distribution process from direct suppliers to small andmedium businesses, both large and small stores, MSMEs, and Village-Owned Enterprises (BUMDES). DCLeu Mart Karawang is the first modern market in Karawang that helps increase MSMEs by simplifying thedistribution process for basic food products and daily necessities based on websites and Androidapplications. To support competition and market opportunities, a study was conducted using SWOTanalysis, STP (Segmenting, Targeting, Positioning), IFE EFE analysis and Marketing Mix 9P accompaniedby a competition analysis of market opportunities, operations, finance, marketing and human resources.The results of this study explain that DC Leu Mart Karawang is very feasible and has good long-termprospects to run. Besides being stated by the results of the analysis, DC Leu Mart Karawang has also beenrunning for approximately 8 months with an increasing trendline every month. This is supported by aReturn on Investment (ROI) of 43.5% and a Payback Period of 2 years and 1 month. The investmentfeasibility results in an NPV of Rp. 7,001,220,721, IRR 51% Net B/C 6.77 and PI 2.16.